A dimensão constitucional do direito de herança: aspectos processuais do inventário e partilha - Andrade, Maria do Céu Pitanga (2006)
The inheritance in Brazil is a main constitucional right foreseen in the article 5th, interpoleted proposition XXX of the Great Letter. It’s a first generation right and as such it must be interpreted and be used. In spite of its constitucional dimension, it is observed that the inventory processes and allotment tend to be slow, hidering and, sometimes, even preventing the access of the heirs to the total property of the possessions left by mortis cause. From this point on, this research demonstrates the importance of the hereditary right inside of the legal context of Brazil, as well as determinated legal aspects of the inventory process and allotment that, when not observed, hold the case up hindering its regular course to the end and attacking the constitucional principle of the effectiveness and the legal security as well as the guarantee of the reasonable time of the process. Amongst the innumerable legal aspects confronted with the inventory processes and allotment, this research approaches: the inventory and its jurisdiction, the performance of the administrator and its respective incidents, the performance of the magistrate, the urgency provisionses at the inventory processes among them the anticipated measures that can be urgent or not as well as the license. Finally this research approaches the procedural moment of the collect of the tax of transmission mortis cause since the entailing demanded by the law tends stopping the processes and damaging its effectiviness, this fact is in disagreement with the spirit of the law. The method used in this research was the bibliographical description. Keywords: